Attitude of healthcare professionals in Türkiye to COVID-19 vaccine. - Gümüştakim, Raziye Şule; Başer, Duygu Ayhan; Cevik, Murat; Güner, Pinar Döner (Eastern Mediterranean Health Journal, 2024)
Background: The COVID-19 vaccine has been effective in reducing infection rates and disease severity; however, vaccination coverage has been lower than expected because of vaccine hesitancy, even among healthcare workers. Aim: To investigate the attitude of healthcare professionals in Türkiye to the COVID-19 vaccine. Methods: This cross-sectional study was conducted between December 2020 and February 2021 among physicians, nurses, midwives, emergency medical technicians, dieticians, and physiotherapists in Türkiye, using the snowball sampling method for data collection. Data were analysed using SPSS version 23 and correlation analysis was conducted to evaluate linear relationship, and multivariate analysis to examine the cause-effect relationship between the variables (α = 0.05). Results: A total of 1057 healthcare professionals participated; average age 38.98 ± 9.044 (min = 19; max = 71), 71.7% (n = 758) women, 69.9% (n = 739) physicians. Of the respondents, 48.3% wanted to be vaccinated whether the vaccine was free or not, 12.1% (n = 128) did not want to be vaccinated and 36.8% were not decided. The most common reasons for wanting to be vaccinated were to end the pandemic (25%, n = 264), seeing vaccination as a good way to prevent COVID-19 disease (30.1%, n = 318), protecting oneself and high-risk individuals from infection (22.2%, n = 235), and hoping that vaccine would reduce the duration and severity of disease (22.9%, n = 242). The most common reasons for not wanting to be vaccinated were fear of side-effects (26.1%, n = 276) and lack of confidence in the reliability of a new vaccine (27.2%, n = 288). The desire to be vaccinated had relationship with influenza vaccination, pneumococcus vaccination, history of COVID-19 infection or contact with a COVID-19 patient, and adherence to infection prevention measures (P < 0.05). Conclusion: Almost half of the healthcare workers in this study were not decided about being vaccinated. To increase acceptance in Türkiye, it is essential to conduct COVID-19 vaccine awareness and education among healthcare professionals because they are perceived as role models in the society, particularly in the health sector.